Works councils and apprenticeship training : heterogeneous works councils, heterogeneous effects? - Weis, Kathrin [Verfasser]; Mühlemann, Samuel [Verfasser]; Pfeifer, Harald [Verfasser] (My University, 2024)
„In Germany, works councils possess co-determination rights concerning apprenticeship training, which may influence training outcomes in firms. While the literature commonly assumes homogeneous effects of works councils, this study reveals considerable heterogeneity in their involvement in training-related decisions. Using representative German firm-level data, we explore two dimensions of works councils' heterogeneity: their participation in various decisions and their success in enforcing agendas. We document the extent to which works councils influence decisions on hiring apprentices, determining the number of apprentices, and retention after training. Our findings indicate that works council participation is associated with higher training propensity and retention rates, but no significant effect on the number of apprentices hired. However, the number of apprentices is notably higher in firms with collective bargaining agreements. Interestingly, works councils that are rated as successful are associated with lower retention rates, highlighting potential conflicts between representing the interests of apprentices and those of other worker groups.” (authors’ abstract; BIBB-Doku)
Keywords: S 3.5.4 Sozialpartner; S 3.2 Unternehmen und Behörden; 370; Betrieb; Betriebsrat; Mitbestimmung; Einflussfaktor; Ausbildungsverhalten